NATIONAL ORIGINALITY OF ARTISTIC IMAGE (Multidisciplinary Journal of Science and Technology, 2026)
This article analyzes the artistic image as a form of reflecting reality in art, in which reality is reinterpreted and generalized through the author's imagination and expressed in a concrete, sensory-perceivable form. The artistic image is not homogeneous: it comprises several levels, the interaction of which provides its artistic depth and polysemy.